Development of hyperkinesias after long-term pallidal stimulation for idiopathic segmental dystonia - Wloch, Andreas; Blahak, Christian; Wolf, Marc (Tremor and other hyperkinetic movements, 2017)
Background:  Chronic deep brain stimulation (DBS) of the globus pallidus internus (GPi) has become an established treatment for dystonia. While bradykinetic symptoms may occur on chronic stimulation, the appearance of hyperkinetic movements has not been well characterized. Case Report:  We report on the development of hyperkinesias after more than 10 years of GPi DBS. Discussion:  Hyperkinesias may evolve upon long-term GPi DBS in dystonia. This might be related to a combined effect consisting of a reduced threshold for effective GPi stimulation for dystonia and spread of current to the globus pallidus externus.